SECUREGRADES: A Web-Based Student Progress Management System with Two-Factor Authentication and Blockchain Implementation for Sekolah Kebangsaan Binjai Jaya (SKBJ) - ehem, MUHAMMAD AZRUL AZIB BIN FAKHRUL ARIFIN; ABD WARIF, NOR BAKIAH (Applied Information Technology And Computer Science, 2024)
A computerized platform called a Student Progress Management System (SPMS) is used to track and evaluate students’ academic progress. Because of security concerns, Sekolah Kebangsaan Binjai Jaya (SKBJ) finds it difficult to allow parental access through the current SPMS. In response, the SecureGrades project was started with the intention of improving the security of the SPMS and enabling safe parental interaction. The Agile technique, a flexible and iterative process, is being used in the development of SecureGrades to make sure the system can adapt to SKBJ’s changing demands. Advanced security features of the system include strong encryption, role-based access control, and two-factor authentication via an app authenticator. In order to add an extra layer of protection, two-factor authentication requires users to submit two forms of verification: their regular password and a special code created by an app. In addition to two-factor authentication for enhanced security, the system now incorporates blockchain technology to ensure the integrity and authenticity of school-issued certificates. This enhancement prevents unauthorized modifications and provides a reliable verification method using QR codes and hash comparison. A safe, user-friendly SPMS that enables parents to interact with their children’s academic data is the SecureGrades project’s anticipated result. This improved method seeks to maintain the highest levels of data protection while promoting increased openness and cooperation between SKBJ and parents.